Seasonal Feeding Preferences of EastAfrican Wild Herbivores Assessed with Stable Carbon Sotope Ratios of Faecal Matter - Tieszen, Larry L.; Onkware, Augustino O. (Africa Environmental Review Journal, 2004)
Stable carbon isotope ratios for grasses and sedges are quantitatively different from those of most forbs, shrubs, and trees in East Africa grazing Systems. Therefore, it is possible to trace this carbon through trophic levels. We repeatedly sampled faecal material from common herbivores in the Maasai Mara Reserve and Nairobi National Park to quantity seasonal resource utilization. Herbivores showed similar trends in consumption of major growth forms at these two sites. Buffalo, hartebeest, topi warthogs, waterbuck, wildebeest, and zebra utilized grasses and sedges throughout wet and dry seasons, but showed slight, but consistent seasonality. Dik-dik, giraffe, and rhinoceros were consistently browsers. Eland also utilized browse for most of the time. Elephant, Grant's gazelle, impala, and Thompson's gazelle were more variable, seasonally, with Thompson's gazelle being more consistent in their preference tor grasses than Grants gazelle. All species consumed a higher proportion of grass at the time of its maximum green biomass. Isotopic analyses provided a powerful and quantitative method to assess resource selectivity in the complex grazing ecosystems. The method is especially useful for quantifying growth form utilization in environments that have strong seasonal variations.